2017
DOI: 10.4014/jmb.1701.01054
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis of Curcumin Glycosides with Enhanced Anticancer Properties Using One-Pot Multienzyme Glycosylation Technique

Abstract: Curcumin is a natural polyphenolic compound, widely acclaimed for its antioxidant, antiinflammatory, antibacterial, and anticancerous properties. However, its use has been limited due to its low-aqueous solubility and poor bioavailability, rapid clearance, and low cellular uptake. In order to assess the effect of glycosylation on the pharmacological properties of curcumin, one-pot multienzyme (OPME) chemoenzymatic glycosylation reactions with UDPα-D-glucose or UDP-α-D-2-deoxyglucose as donor substrate were emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…While the Cur group showed the weak green florescence because of the curcumin inside the cells. The poor aqueous solubility of curcumin influenced the internalization efficiency into the cells, which further reduced its therapeutic efficacy 25,26. After 4 hrs of incubation, the green fluorescence intensity in Gal-BSA-Cur NPs group was stronger than that in the Cur group, which indicated that Gal-BSA NPs could enhance the ability of internalization of curcumin into the cells and release more curcumin in the cytoplasm as well as in the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…While the Cur group showed the weak green florescence because of the curcumin inside the cells. The poor aqueous solubility of curcumin influenced the internalization efficiency into the cells, which further reduced its therapeutic efficacy 25,26. After 4 hrs of incubation, the green fluorescence intensity in Gal-BSA-Cur NPs group was stronger than that in the Cur group, which indicated that Gal-BSA NPs could enhance the ability of internalization of curcumin into the cells and release more curcumin in the cytoplasm as well as in the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…Glycosides are secondary metabolites that widely exist in all organs of plants, such as flowers, fruits, leaves, skins, and roots, etc ( Gruner et al, 2002 ), and previous studies found that glycosides had a wide range of pharmacological activities, such as antiviral ( Chen W. et al, 2019 ; Khodair et al, 2019 ), antibacterial ( Mohammed et al, 2019 ), anticancer ( Gurung et al, 2018 ; Rahim et al, 2020 ), antioxidant ( Jiang et al, 2018 ; Hawas et al, 2019 ), and anti-HIV ( He et al, 2019 ) activities. Meanwhile, studies also found that glycoside derivatives showed exceeding inhibitory activities against plant pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was also found that glycosylation is one of the effective ways to improve the functional activity of active lead compounds and develop new drugs. ( Gurung et al, 2018 ; Wu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding its anti-cancer properties, clinical trial and pharmacokinetic data on curcumin displayed poor absorption and bio distribution, low bioavailability [ 17 , 18 , 19 ], inadequate biological stability [ 20 ], poor aqueous solubility [ 20 , 21 ], rapid metabolism [ 22 ], and rapid systemic elimination [ 19 , 23 ]. Curcumin which is hydrophobic [ 20 ] undergone biotransformation into curcumin glucuronides in the intestine and liver [ 24 , 25 ], which it is rapidly metabolized [ 22 ] and eliminate via feces [ 20 , 23 , 26 ].…”
Section: Introductionmentioning
confidence: 99%